Design and validation of two measures to detect anxiety disorders in epilepsy: The Epilepsy Anxiety Survey Instrument and its brief counterpart. (27th September 2019) - Scott, Amelia J.; Sharpe, Louise; Thayer, Zoe; Miller, Laurie A.; Hunt, Caroline; MacCann, Carolyn; Parratt, Kaitlyn; Nikpour, Armin; Wong, Toh; Gandy, Milena
Abstract: Objective: The study objective was to develop and validate the first epilepsy‐specific anxiety survey instrument (Epilepsy Anxiety Survey Instrument [EASI]) alongside a briefer screening instrument to detect anxiety disorders in routine clinical practice (brEASI). Methods: The instruments were developed utilizing a mixed‐methods approach in four related studies. Pilot items were developed following qualitative interviews with people with epilepsy (PWE; Study 1) and consultation with multidisciplinary experts in anxiety and epilepsy (Study 2). PWE (n = 314) then completed pilot items alongside existing measures of anxiety and depression (Study 3). Factor analysis was conducted to refine the scale and select well‐performing items for a briefer diagnostic screener (brEASI). The brEASI was validated against a gold standard diagnostic interview in 106 PWE recruited from an outpatient epilepsy service (Study 4). Receiver operating characteristic analysis was conducted to determine the brEASI's diagnostic performance. Results: Twenty‐six pilot items were generated based on the findings of Studies 1 and 2. Analyses in Study 3 resulted in an 18‐item EASI, and eight well‐performing items were selected for the brEASI. The area under the curve (AUC) of brEASI was excellent (AUC = 0.89, 95% confidence interval = 0.82‐0.94). At a cutoff of 7, it demonstrated a sensitivity of 76% and specificity of 84% for identifying Diagnostic and Statistical Manual of Mental Disorders, 5th edition anxiety disorders. Significance: The EASI and brEASI represent the first valid and reliable epilepsy‐specific anxiety instruments. The EASI has been designed to comprehensively assess anxiety in PWE, whereas the brEASI may be used within busy neurology settings to provide rapid information to aid diagnoses of anxiety disorders. Given the significant prevalence and burden of anxiety in PWE, these tools are important potential solutions to improve the understanding and detection of anxiety in epilepsy.